PREDICTORS OF THE SENSE OF BELONGING TO THE COUNTRY: EXPLORING A NEW MODEL - Koļesovs, Aleksandrs; Melne, Ieva (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
This study explored new possibilities for measuring the sense of belonging to the country and investigated predictors of the sense of belonging to Latvia. Focusing on students’ sense of belonging to the country is explained by two reasons: 1) emigration is the main factor of depopulation in Latvia; 2) students’ intention to emigrate is the highest among other social groups. Studies in the field of community psychology present models of the sense of community and explore intentions to stay in a particular place. Within a new model, different levels of social systems (from meso- to macro-system) were included into the analysis of predictors of the sense of belonging to the country. The participants were 205 university students from 18 to 30 (67% females). On the basis of previous studies, a new measure of the sense of belonging and perceived context was developed. The results confirmed a complex model of the sense of belonging in the context of social systems. Higher perceived opportunities at the level of the country and more positive evaluation of the future of Latvia predicted higher level of the sense of belonging to Latvia directly. In addition, female students perceived higher level of the sense of belonging than male students.